Multiproduct Cost Function Estimation for American Higher Education: Economies of Scale and Scope - Balazs Varadi (Hungarian Academy of Sciences, Institute of Economics, 2001)
Following Cohn, Rhine and Santos (1989) and Koshal and Koshal (1999),we use American data, i.e., a matched data set of 730 private and 820 public colleges and universities, to estimate multi-product cost functions in higher education. We use federal research grants as a proxy for research output and independent rankings of colleges as a quality proxy. We found that private and public schools have different cost functions. We obtained robust cost functions for private institutions. In those schools, economies of scope are present throughout. There are also economies of scale to a point that is above the size of an average private institution. The marginal cost of educating undergraduates is decreasing, while that of graduate students is increasing. The value of the endowment of private institutions is positively correlated with their costs.
Keywords: 330